2007
DOI: 10.1002/path.2218
|View full text |Cite
|
Sign up to set email alerts
|

Augmented gp130‐mediated cytokine signalling accompanies human gastric cancer progression

Abstract: H. pylori infection accounts for most cases of gastric cancer, but the initiating events remain unclear. The principal H. pylori pathogenicity-associated CagA protein disrupts intracellular SHP-2 signalling pathways including those used by the IL-6 family cytokines, IL-6 and IL-11. Imbalanced IL-6 family cytokine signalling in the gp130(757FF) mouse model of gastric cancer arising from hyperactivation of oncogenic STAT3 after altered SHP-2 : ERK1/2 signalling produces dysplastic antral tumours preceded by gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
91
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(99 citation statements)
references
References 37 publications
6
91
1
1
Order By: Relevance
“…In gastric cancer, the expression of molecules associated with this pathway has been related to a worse prognostic, to a VEGF over expression (Gong et al, 2005), and to a shorter survival post-surgery (Yakata et al, 2007). In addition, the activation of STAT3 and ERK 1/2 is increased in stomach samples of patients infected with H. pylori, and these increases are likely Intestinal gastric cancer markers related to inflammation R Mejías-Luque et al driven in an IL-6-dependent manner, whereas IL-11 is upregulated in gastric adenocarcinoma regulating epithelial cell turnover (Jackson et al, 2007). The inflammatory cells infiltrating human colorectal tumors have been recently characterized in a large cohort of samples, and in these tumors the type, density, and location of the immune cells have a prognostic value superior to the histopathological methods currently used to stage colorectal cancer (Galon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, the expression of molecules associated with this pathway has been related to a worse prognostic, to a VEGF over expression (Gong et al, 2005), and to a shorter survival post-surgery (Yakata et al, 2007). In addition, the activation of STAT3 and ERK 1/2 is increased in stomach samples of patients infected with H. pylori, and these increases are likely Intestinal gastric cancer markers related to inflammation R Mejías-Luque et al driven in an IL-6-dependent manner, whereas IL-11 is upregulated in gastric adenocarcinoma regulating epithelial cell turnover (Jackson et al, 2007). The inflammatory cells infiltrating human colorectal tumors have been recently characterized in a large cohort of samples, and in these tumors the type, density, and location of the immune cells have a prognostic value superior to the histopathological methods currently used to stage colorectal cancer (Galon et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 inhibits the FasL-induced apoptosis in GECs though without significant effect on the transcription of Fas (Guo et al, 2006). IL-11 activates the STAT3 like IL-6 and concomitantly increases proliferation of GECs (Jackson et al, 2007). Some other molecules including cyclooxygenase-2 (COX-2), prostaglandin E2 (PGE2), nitric oxide (NO), inducible NO synthase (iNOS), monocyte chemoattractant protein 1 (MCP1), and hepatocyte growth factor (HGF) and c-MET also relate to GC-associated inflammatory responses (Zhuang X et al, 2001;Futagami et al, 2008;Snider & Cardelli, 2009;Cho et al, 2010).…”
Section: Inflammatory Responsesmentioning
confidence: 99%
“…9 Numerous in vitro studies have shown that STAT3 promotes proliferation and invasion of gastric cancer cells, 10,11 and upregulates expression of potent angiogenic factors.…”
Section: Stat3 As a Prognostic Marker In Human Gastric Cancermentioning
confidence: 99%
“…In contrast to the rodent model, moderate alcohol consumption in humans is reported to increase serum adiponectin levels. [9][10][11] However, the overall importance of adiponectin in heavy drinkers and in patients with severe ALD has not yet been evaluated.…”
mentioning
confidence: 99%
See 1 more Smart Citation